The Role Of Tibb Al-Nabawi In Modern Healthcare And Wellness - Mohammed Husni Mannarmala (Penerbit Hellow Pustaka, 2026)
This study examines the contemporary relevance of Tibb al-Nabawi (Prophetic Medicine) within modern healthcare, highlighting its role as a holistic, preventive, and spiritually grounded system of well-being. Rooted in the teachings of Prophet Muhammad (peace be upon him), Tibb al-Nabawi integrates physical, emotional, and spiritual dimensions of health, offering principles that align closely with today’s preventive medicine, including moderation in diet, hygiene, fasting, physical activity, and balanced living. The paper explores widely practiced Prophetic remedies—such as honey, black seed, dates, Hijāmah (cupping), and spiritual therapies like duʿā’, Qur’anic recitation, and dhikr—and examines how modern scientific studies increasingly validate their therapeutic benefits in areas such as immune function, metabolic regulation, cardiovascular balance, and mental resilience. In addition, the research highlights the gradual incorporation of Tibb al-Nabawi into Complementary and Alternative Medicine (CAM) and integrative health models across hospitals and wellness programs, particularly through herbal treatments, dietary counselling, and culturally sensitive spiritual care. The study further discusses advancements in scientific methodologies, including randomized controlled trials (RCTs) and analytical tools such as High-Performance Liquid Chromatography (HPLC), which contribute to the standardization, safety, and evidence-based evaluation of Prophetic remedies. Moreover, the paper surveys emerging technological developments—such as mobile health applications, telemedicine, artificial intelligence (AI), wearable devices, and blockchain systems—that support personalized, secure, and accessible delivery of Prophetic medical guidance. Overall, this study demonstrates that Tibb al-Nabawi presents a timeless, ethically grounded, and scientifically compatible framework for modern integrative healthcare, offering a patient-centred and spiritually enriched approach that aligns with global shifts toward holistic wellness.